Associations of Serum Folate and Holotranscobalamin With Cardiometabolic Risk Factors in Rural and Urban Cameroon. (7th June 2021) - Mba, Camille; Koulman, Albert; Sharp, Stephen; Forouhi, Nita; Imamura, Fumiaki; Assah, Felix; Mbanya, Jean Claude; Wareham, xsNicholas
Abstract: Objectives: Previous studies mostly in Western populations suggest that a low exposure to B-vitamins (folate and vitamin B12 in particular) are associated with increased cardiometabolic disease risk. This study aimed to examine the association of blood concentrations of folate and holotranscobalamin (holoTC) with cardiometabolic risk factors in adults in Cameroon. Methods: We conducted a cross-sectional population-based study in 497 adults. We measured serum folate and holoTC by liquid chromatography tandem mass spectrometry and "sandwich" ELISA respectively. Total folate was calculated excluding the oxidation product 5-methyltetrahydrofolate. The outcomes were individual cardiometabolic risk factors and a continuous metabolic risk score. We fitted linear regression models to examine the association between B-vitamins and cardiometabolic risk factors and estimated β-coefficients and 95% confidence intervals per standard deviation (SD) difference in each B vitamin variable. Results: Mean age was 38.2 (SD: 8.6) years and 63.5% of the participants were women. Mean serum folate was 15.9 (SD: 10.8) nmol/L and holoTC was 74.1 (SD: 33.7) pmol/L. Rural residents had higher concentrations of serum folate but lower holoTC than urban residents. There was a significant inverse association between serum folate and the metabolic risk score (−0.22 (−0.41 to −0.03)) in a multivariable model adjusted for age, sex, education level, smoking, alcohol intake, rural/urban site and BMI. This association was attenuated to the null after further adjustments for objectively measured physical activity (PAEE) and holoTC. HoloTC was positively associated with the metabolic risk score in unadjusted analysis (0.29 (0.08 to 0.51)) but attenuated to the null after adjusting for socio-demographic characteristics. For individual risk factors, an inverse association was observed between serum folate and diastolic blood pressure, which was unaffected by adjustment for confounders including PAEE and holoTC (−1.18 (−2.16 to − 0.20)). Conclusions: In Cameroon, serum folate and holoTC were associated with the metabolic risk score in opposite directions, partly depending on potential demographic and socioeconomic characteristics. The inverse association between serum folate and the metabolic risk score was likely driven by the blood pressure component. Funding Sources: None.